2021
DOI: 10.1002/ski2.59
|View full text |Cite
|
Sign up to set email alerts
|

How has the COVID‐19 pandemic affected eczema self‐management and help seeking? A qualitative interview study with young people and parents/carers of children with eczema

Abstract: Background Eczema can have a considerable impact on quality of life. Treatments can improve this, but management is complex. Barriers to eczema self‐management may be impacted upon by environmental context, such as the COVID‐19 pandemic. Objectives To explore experiences of eczema, self‐management, and accessing healthcare and advice during the COVID‐19 pandemic among young people with eczema and parents/carers of children with eczema. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%
“…Some of the recruitment and follow-up of participants in this study took place during the covid-19 pandemic. Qualitative research carried out during the trial suggested that this could have had both positive and negative impacts on participants’ eczema 43. For example, it may have made it harder for participants to access healthcare for some months during the study and to discuss or change their treatments in response to the intervention, although this lack of access may have improved engagement with the online toolkits.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research carried out during the trial suggested that this could have had both positive and negative impacts on participants' eczema. 43 For example, it may have made it harder for participants to access healthcare for some months during the study and to discuss or change their treatments in response to the intervention, although this lack of access may have improved engagement with the online toolkits. In some contexts, the effectiveness of online interventions has been shown to be enhanced by health professional support, and this was tested in a feasibility study before this trial.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…However, neither survey provided in‐depth insight into factors influencing people's decisions. To date, a small number of qualitative studies have explored help‐seeking during the COVID‐19 pandemic, but only included patients with specific health conditions (Ferry et al, 2021 (coronary heart disease); Steele et al, 2021 (eczema)).…”
Section: Introductionmentioning
confidence: 99%